Optimising acute body mass management practices in Australian Olympic combat sports - Reale, R. J. (University of the Sunshine Coast, 2017)
Unarmed Olympic combat sports include the striking sports of boxing and taekwondo and the grappling sports of judo and wrestling. All of these sports separate competitors into weight divisions, attempting to reduce physical differences and create 'an even playing field'. It is common for these athletes (and those in other weight category sports) to undertake both chronic and rapid weight loss (RWL) prior to competition in an attempt to obtain a competitive edge over smaller opponents. Recognising this, reviews and guidelines have been established to assist with optimising chronic body mass (BM) management in combat sport athletes. However no consolidated guidelines for RWL exist, despite the vast majority of combat sport athletes engaging in these practices. Thus the overarching aim of this body of work was to complement existing chronic BM guidance by developing pragmatic guidelines and recommendations regarding acute BM manipulation to assist Australian Olympic combat sport athletes.